"I thought I was prepared to do this": an exploration of the learning and development of leadership coaches. Issue 4 (21st September 2021) - Huggins, Kristin Shawn; Klar, Hans W.; Andreoli, Parker M.
Abstract : Purpose: The purpose of this paper was to determine what experienced school leaders learned through participating in a three-year leadership initiative, called the Leadership Learning Community (LLC), that helped them coach less experienced leaders to lead school improvement efforts. Design/methodology/approach: Data were collected and analyzed using a qualitative design throughout the three-year initiative. Findings: The findings indicate the LLC leadership coaches learned to accept and navigate the leaders' developmental and contextual needs, practiced and honed their coaching skills and recognized their own developmental needs. Originality/value: These findings address the paucity of research on leadership coach learning and development.